BACTERIA PATTERN OF URINE CULTURE FROM PATIENTS WITH DIABETES AT DR RAMELAN NAVY HOSPITAL SURABAYA, INDONESIA - Libriansyah, Libriansyah; Rifiana, Hilda; Soelistijo, Soebagijo Asi (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The presence of a bacteria pattern that is thought to be the cause of the infection is essential for the basis of empirical and definitive antibiotic treatment. The study aimed to find the bacteria pattern of urine culture from patients with diabetes. METHODOLOGY This was a descriptive, cross-sectional study. The sample was pus obtained from the 3rd grade of patients with diabetic foot who had clear signs of infection, and were hospitalized at Dr. Ramelan Navy Hospital in the period of 2016 to 2018 (3 years). Pus was taken before antibiotic administration, and the culture was done in the microbiology laboratory. RESULTS The number of pus samples collected was 1571 samples. Isolates that have bacterial growth and can be identified were 1328 samples (84.53%). Bacterial isolates found as the most common cause were Escherichia coli 17.17% (228). The second most prevalent bacterial isolates were Staphylococcus aureus (157 isolates). While the third rank in 2016, 2017 and 2018 were Burkholderie pseudomallei (35 isolates), Klebsiella pneumonia (39 isolates) and P. aureginosa (50 isolates) respectively. Meropenem and Piperacillin were found as the sensitive antibiotics in these patients in 2016. While no antibiotic was sensitive for E. coli, but meropenem, piperacillin and vancomycin were found sensitive for S. aureus and others in 2017. In 2018, E. coli was found sensitive to Amikacin and Meropenem, whereas other types of bacteria were resistant to antibiotics examined. CONCLUSION It was found that the most prevalent bacteria that cause diabetic foot infections in patients with diabetes mellitus were Escherichia coli.